Finding purpose in the conservation of biodiversity by the commingling of science and ethics - Vucetich, JA; Macdonald, EA; Burnham, D; Bruskotter, JT; Johnson, D; Macdonald, D (MDPI, 2021)
Averting the biodiversity crisis requires closing a gap between how humans tend to behave, individually and collectively, and how we ought to behave – “ought to” in the sense of behaviors required to avert the biodiversity crisis. Closing that gap requires synthesizing insight from ethics with insights from social and behavioral sciences. This article contributes to that synthesis, which presents in several provocative hypotheses: (i) Lessening the biodiversity crisis requires promoting pro-conservation behavior among humans. Doing so requires better scientific understanding of how one’s sense of purpose in life affects conservation-relevant behaviors. Psychology and virtue-focused ethics indicate that behavior is importantly influenced by one’s purpose. However, conservation psychology has neglected inquiries on (a) the influence of one’s purpose (both the content and strength of one’s purpose) on conservation-related behaviors and (b) how to foster pro-conservation purposes; (ii) Lessening the biodiversity crisis requires governance – the regulation of behavior by governments, markets or other organization through various means including laws, norms, and power – to explicitly take conservation as one of its fundamental purposes and to do so across scales of human behaviors, from local communities to nations and corporations; (iii) Lessening the biodiversity crisis requires intervention via governance to nudge human behavior in line with the purpose of conservation without undue infringement on other basic values. Aligning human behavior with conservation is inhibited by the underlying purpose of conservation being underspecified. Adequate specification of conservation’s purpose will require additional interdisciplinary research involving insights from ethics, social and behavioral sciences, and conservation biology.